European Integration of Albania : Economic Aspects - Elke Thiel (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2004)
Albania has been partner of the Stability Pact for South Eastern Europe and the EU Stabilisation and Association process for the Western Balkan from the beginning. European integration requires very fundamental and far reaching reforms. Albania has faced the challenge, but in many cases reform measures are not yet properly implemented. Macroeconomic performances have improved recently, and there are some encouraging signs that foreign business might be ready to invest in the country. Yet uncertainties and deficiencies in the political system remain a major risk. – – Albanien ist Partner im Stabilitätspakt für Südosteuropa und im Stabilisierungs- und Assoziierungsprozess der EU. Die europäische Integration verlangt grundlegende Reformen, die Albanien zum Teil eingeleitet hat, die aber häufig in Justiz und Verwaltung noch nicht umgesetzt wurden. Der sich abzeichnende Wirtschaftsaufschwung und ausländische Investitionsbereitschaft könnten durch politische Unsicherheiten in Gefahr geraten.
Keywords: 330; Albanien; EU-Stabilisierungs- und Assoziierungsprozeß für den westlichen Balkan; Systemreformen; Fortschrittsbericht der EU-Kommission; Albania; EU Stabilisation and Association process for the Western Balkan; system reforms; EU assessment report; experts recommendations; Assoziierung; EU-Erweiterung; Wirtschaftliche Anpassung; Albanien